Governing private foundations using the tax law - Sansing, Richard; Yetman, Robert (Journal of Accounting and Economics, 2006)
This paper investigates two tax law provisions that act as governance instruments designed to regulate the behavior of private foundations. It examines tax return data from a sample of private foundations to determine the effects of the minimum distribution requirement and the dual tax rate regime. The minimum distribution requirement primarily affects the distribution behavior of foundations that are no longer receiving donations and are growing more slowly than the average foundation. The dual tax rate regime has countervailing effects on distributions by foundations, rewarding both higher levels of current distributions and lower levels of prior year distributions.